PENDAMPINGAN PEMASARAN, LEGALITAS DAN PENERAPAN TEKNOLOGI TEPAT GUNA (TTG) KEPADA PELAKU USAHA MIKRO, KECIL DAN MENENGAH (UMKM) KERIPIK PISANG - Anggita Arkin Dwi Pradita; Syifa Fauziah; Desti Rahmawati; Mohamad Syaripudin; Encep Saefullah (Indonesian Collaboration Journal of Community Services, 2022)
The problems that occur to the SMEs of Banana Chips in Kamurang Village, Cikande District, Serang Regency are that product marketing is still conventional, business product do not have a license and the production process still uses traditional tools. The purpose of this community service activity is to provide assistance to Banana Chips SMEs in Kamurang Village, Cikande District, Serang Regency related to the problems they face. The implementation method of this community service activity is a chronological or gradual strategy which includes the stages of preparation, implementation and evaluation. The result of the implementation of this activity is that the Banana Chips MSME actors have used the e-commerce platform as a marketing medium for their products, obtained a Business Identification Number (NIB) and a Micro Small Business License (IUMK) as a business product license and using a banana slicer for the production process as the application Appropriate Technology (TTG). By using a positive approach in the form of a participatory, reflective and innovative approach, Banana Chips SMEs are expected to be able to compete with other types of businesses